Job Satisfaction of U.A.E. Dental Practitioners - Al-Buainain, Fajer S.; Alzarouni, Asma A.; Alshamsi, Hissa A.; Arab, Arwa H.; Bader, Fares; Awad, Manal (European Journal of Dentistry, 2019)
Objective The study aims to analyze job satisfaction among registered clinical dentists in the United Arab Emirates (UAE), and also to explore satisfaction with different work environmental factors and relate them to overall job satisfaction.Materials and Methods A survey modified from the American Dental Association version of job satisfaction published in 2013 to 2014, was given to 197 licensed dentists in Dubai and Sharjah cities in the UAE. The questionnaire included four main sections, in addition to the demographic factors questions. All questions were answered using the 5-point Likert scale. The only exception was the comfortability in the working environment which was answered using a 3-point Likert scale.Statistical Analysis Categorical data were presented as frequencies and percentages, and data were analyzed using means and standard deviations. Regression analysis was performed with overall job satisfaction as the dependent variable and seven aspects of satisfaction with work and individual characteristics as the independent variables. An α level of 0.05 was used for tests of statistical significance.Results The overall job satisfaction of dentists working in the UAE is high compared with other countries. Highest satisfaction was related to the relationship with patients, colleagues, and staff. On the other hand, the least satisfaction was linked to the opportunity for part-time work and benefits package. There were no significant differences between male and female participants regarding all work-related factors apart from autonomy. However, private sector dentists had a higher level of satisfaction compared with the public sector in many work-related factors.Conclusion There are various dimensions that collectively influence the level of overall job satisfaction. Difference existing between the levels of job satisfaction among private and public sector dentists and between male and female dentists need to be addressed to increase the level of job satisfaction among UAE dentists and thus improve all dental care system.
Keywords: job satisfaction; dentist; public sector; private sector; work environment factors